Proposal of Ancylothrix gen. nov., a new genus of phormidiaceae (Cyanobacteria, Oscillatoriales) based on a polyphasic approach - Martins, Mariellen Dornelles [UNESP]; Rigonato, Janaina [UNESP]; Taboga, Sebastião Roberto [UNESP]; Branco, Luis Henrique Zanini [UNESP] (Microbiology Society, 2016)
During a study about the diversity of Phormidioideae (Phormidiaceae, Oscillatoriales) in Brazil, seven strains from southern and southeastern regions were isolated in monospecifc cultures and submitted to polyphasic evaluation (morphological, ecological, cytological and molecular studies). The populations studied were found to be morphologically similar to Kamptonema (filaments narrowed and bent at the end) and cytologically different (thylakoids' arrangement - radial distribution in Brazilian strains and parietal distribution in Kamptonema). The original habitats were very diverse among the Brazilian strains (freshwater, wet soil and barks of trees). Phylogenetic analysis based on 16S rRNA gene sequences revealed that the strains were placed together in a very distinctive and highly supported clade. Thus, the set of characteristics of the strains resulted in the recognition of the new genus Ancylothrix Martins et Branco gen. nov. with two species [Ancylothrix rivularis gen. nov., sp. nov. (type species) and Ancylothrix terrestris sp. nov.], distinguishable by differences in genetic and ecological characteristics and described under the provisions of the International Code of Nomenclature for algae, fungi and plants. Secondary structures of D1-D1', box-B and V3 regions were conserved in A. rivularis gen. nov. sp. nov. and more variable in A. terrestris sp. nov.
Keywords: 16S rRNA; 16S-23S ITS; Brazil; Morphological evaluation; Phylogenetic analysis; Taxonomy